Contribution of the Endosomal-Lysosomal and Proteasomal Systems in Amyloid-β Precursor Protein Derived Fragments Processing - Evrard, Caroline; Kienlen-Campard, Pascal; Coevoet, Mathilde; Opsomer, Rémi; Tasiaux, Bernadette; Melnyk, Patricia; Octave, Jean-Noël; Buée, Luc; Sergeant, Nicolas; Vingtdeux, Valérie (Frontiers in Cellular Neuroscience, 2018)
Abeta peptides, the major components of amyloid deposits of Alzheimer’s disease, are released following sequential cleavages by secretases of its precursor named the amyloid precursor protein (APP). In addition to secretases, degradation pathways, in particular the endosomal/lysosomal and proteasomal systems have also been reported to contribute to APP processing. However, the respective role of each of these pathways towards APP metabolism remains to be established. To address this, we used HEK 293 cells and primary neurons expressing full-length APPWT or the beta-secretase-derived C99 fragments (beta-CTFs) in which degradation pathways were selectively blocked using pharmacological drugs. APP metabolites, including carboxy-terminal fragments (CTFs), soluble APP (sAPP) and Abeta peptides were studied. In this report, we show that APP-CTFs produced from endogenous or overexpressed full-length APP are mainly processed by gamma-secretase and the endosomal/lysosomal pathway, while in sharp contrast, overexpressed C99 alone is mainly degraded by the proteasome and to a lesser extent by gamma-secretase.